Global increases of salt intrusion in estuaries under future environmental conditions - Jiyong Lee; Bouke Biemond; Daan van Keulen; Ymkje Huismans; René M. van Westen; Huib E. de Swart; Henk A. Dijkstra; Wouter M. Kranenburg (Nature Communications)
Abstract In recent years, increased salt intrusion in surface waters has threatened freshwater availability in coastal regions worldwide. Yet, current future projections of salt intrusion are limited to local regions or changes to single forcing agents. Here, we quantify compounding contributions from changes in river discharge and relative sea level to changing future salt intrusion under a high-emission scenario (Shared Socioeconomic Pathway, SSP3-7.0) for 18 estuaries around the world. We find that the annual 90th percentile future salt intrusion is projected to increase between 1.3% and 18.2% (median 9.1%) in 89% of the studied estuaries worldwide. Our analysis also indicates that, on average, sea-level rise contributes approximately two times more to increasing future salt intrusion than reduced river discharge. We further show that the return levels of present-day 100-year salt intrusion events are projected to increase between 3.2% and 25.2% (median 10.2%) in 83% of the studied estuaries.